No difference in outcomes in a matched cohort of operative versus nonoperatively treated displaced medial epicondyle fractures. Issue 6 (November 2019) - Axibal, Derek P.; Ketterman, Brian; Skelton, Anne; Carry, Patrick; Georgopoulos, Gaia; Miller, Nancy; Mayer, Stephanie W.
Abstract : The purpose of our study was to compare the treatment outcomes and complications between operatively and nonoperatively treated displaced medial epicondyle fractures. Pediatric patients treated for an acute, displaced medial epicondyle fracture between 2005 and 2015 were retrospectively reviewed. A total of 22 operative participants were matched to 22 nonoperative participants, with an average displacement of 9.7 mm in both groups. There was no statistical difference in average length of immobilization, median time to full pronation/supination and flexion/extension, proportion of patients needing physical therapy, and complications. There were no statistical differences in outcomes between operative and nonoperatively treated, moderately displaced, pediatric medial epicondyle fractures. This suggests that operative and nonoperative interventions show equivalent outcomes for these injuries.